Expert consensus on standardized management of tumor gene sequencing for cancer patients - Mengjia Qian; Yanxia Zhan; Lili Ji; Hao Chen; Yunfeng Cheng (Wiley, 2023)
Abstract Background Tumour gene detection by next‐generation sequencing (NGS) can comprehensively analyze the molecular characteristics of tumors, and predict drug efficacy and tumor resistance mechanisms through tumour cell models, thereby realizing individualized and precise treatment. Therefore, the whole process of standardized management is required. This consensus aims to refine the standardized management of tumor gene sequencing for cancer patients based on the NGS platform, hoping to provide help for the personalized treatment of cancer patients, and further promoting the development of precision medicine. Methods and results Standardized management for tumour gene detection of cancer patients includes patient management before gene testing, during gene testing, and after gene testing. Tumour patients should select appropriate test samples and test content before receiving genetic testing. There should be a clear informed consent statement during the test, a detailed report should be provided after the test, and counseling and monitoring follow‐up should be provided. The management of genetic testing of tumour patients should cover early screening and early diagnosis of tumors, molecular classification and companion diagnosis of tumours, and monitoring of tumour recurrence. Conclusion Effective management and standardized procedures for gene detection of cancer patients, covering the whole process before, during and after detection, will benefit the majority of patients from early screening, personalized diagnosis and treatment, prognosis evaluation and other aspects of cancer, and promote the healthy development of the precision medicine industry.